1974
DOI: 10.1258/002367774780943913
|View full text |Cite
|
Sign up to set email alerts
|

Zinc deficiency in female rabbits

Abstract: SUMMARYZinc deficiency was induced in recently weaned female Tan rabbits by feeding a diet containing 0·2 p.p.m. of zinc and severely limiting their access to zinc from other sources in the environment. Reduced food consumption, weight loss, lowered haematocrit leve]s, frequent appearance of alopecia and dermatosis as well as reproductive failure were observed. Histo]ogically, the uteri of the zinc-deficient rabbits were pale and inactive. The ovaries had Graafian follicles but lacked corpora ]utea despite rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Zinc deficiency in female rabbits resulted, according to a study, in disinterest in their male counterparts and in failure of ovulation [26]. Another study demonstrated that Zn deficiency could lead to abnormal estrous cycles in female rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc deficiency in female rabbits resulted, according to a study, in disinterest in their male counterparts and in failure of ovulation [26]. Another study demonstrated that Zn deficiency could lead to abnormal estrous cycles in female rats [27].…”
Section: Discussionmentioning
confidence: 99%
“…Although alopecia has been documented in dietary ZD AE mouse [67], rat [68,69], and rabbit [70] models, none of these models have shown the mechanism of alopecia in AE. In summary, although Zn deficiency appears to drive the hair cycle to telogen effluvium and to induce abnormal hair keratinization, the underlying mechanism, even in AE animal models, is still unknown (Fig.…”
Section: Alopecia In Aementioning
confidence: 99%
“…In females, dietary zinc deficiency causes developmental problems throughout pregnancy (28 -30). Prolonged zinc deficiency in rabbits causes decreased mating frequency and lack of corpus luteum (CL) formation (31). Recently, a role for zinc in the completion of meiosis I was demonstrated in vitro (32)(33)(34).…”
mentioning
confidence: 99%